ANALISIS FAKTOR PENYEBAB KURANGNYA SOPAN SANTUN ANAK SEKOLAH DASAR KELAS V SDN SINDANGGALIH - Nuriadin, Saban; Fajar Pratama, Febri; Chandra, Deni (JIPIS, 2025)
Research on the factors causing the lack of good manners among elementary school children is very important. in the digital era and rapid social change, understanding these factors is important to adapt educational approaches to current developments. This research aims to examine the factors that cause children's lack of good manners in elementary schools and to examine the manners reflected by fifth grade students at SDN Sindanggalih. This research uses a descriptive qualitative method because it involves direct study of the research subject. This method relies on postpositivism philosophy and aims to understand the natural conditions of the research object. The researcher acted as the main instrument in collecting data through triangulation, and data analysis was carried out qualitatively based on the results of research findings regarding the factors causing the lack of good manners in class V elementary school children at SDN Sindanggalih. There are several factors that influence the lack of good manners in elementary school children. The formation of students' polite character is greatly influenced by education, be it education in the family, education in the community environment, and education in the school environment. The factors that cause the lack of good manners in elementary school children are usually obtained from the environment and indeed their character is like that. It is not enough if children are given polite lessons only at school. Again, the basis for forming students is from their family environment.